Anterior cerebral artery occlusion with middle cerebral artery stenosis successfully treated with endovascular thrombectomy and penumbra salvage in the middle cerebral artery territory: A case report - Tsubasa Okuyama; Saori Kubota; Hiromichi Oishi; Satoshi Ishige; Toshio Machida (Interdisciplinary Neurosurgery, 2023)
Background: In the anterior circulation, the indications and efficacy of mechanical thrombectomy for internal carotid artery occlusion and middle cerebral artery occlusion have been established. However, no rigid treatment standard has been established for anterior cerebral artery occlusion. We report a case of anterior cerebral artery occlusion (ACAO) caused by cardiogenic cerebral embolism with diffuse stenosis of the horizontal portion of the middle cerebral artery (MCA), in which thrombectomy was performed to ACAO and salvage of the MCA territory penumbra was achieved. Case description: A 77-year-old woman with atrial fibrillation presented to the emergency room with left hemiparesis and left hemispatial agnosia. She had stenosis of the right middle cerebral artery and occlusion of the right anterior cerebral artery. Ischemic symptoms were judged to be caused due to decreased blood flow in the collateral circulation because of occlusion of the right anterior cerebral artery, and thrombectomy was performed. Complete recanalization was achieved, and the ischemic symptoms in the right middle cerebral artery region showed improvement. Conclusion: In cases of clinically suspected ischemia in the middle cerebral artery territory, it may be possible to salvage the penumbra by reperfusion even if the imaging diagnosis is occlusion of the anterior cerebral artery.